A Crime Prevention Framework for CVE - Hardy, Keiran (Terrorism and political violence, 2022)
CVE is a diverse policy space involving efforts to build cohesive communities, support young people who are vulnerable to radicalization, and deradicalize convicted terrorism offenders. Recently, the public health model of disease prevention has become an influential framework for understanding these diverse components. In this paper, I argue that crime prevention should be preferred as a conceptual framework for CVE. I offer a criminological framework encompassing situational prevention, developmental prevention, community crime prevention, third-party policing and procedural justice policing. I develop these concepts into an agenda for crime prevention research in CVE. I also briefly outline some of the lessons that the evidence base from criminology may provide when designing CVE programs and policy.